PROFIT-AND-LOSS SHARING FINANCING, OPERATING EXPENSES, AND THE INTERMEDIATION COSTS OF ISLAMIC RURAL BANKS IN INDONESIA - Robiatun NB, Fahmia; Susamto, Akhmad Akbar; Saleh, Samsubar (Journal of Islamic Monetary Economics and Finance, 2024)
This paper examines the effect of profit-and-loss sharing financing (PLS financing) and operating expenses on the intermediation costs of Islamic rural banks in Indonesia. Using a panel dataset of 147 Islamic rural banks over the period 2011-2021 and dynamic panel regressions, it shows that, in general, PLS financing exerts no significant influence on the Islamic rural banks’ intermediation costs, as measured by the net margin. Meanwhile, the operating expenses are significantly and positively affecting the banks’ net margin, the result that is robust to different regression specifications. Accordingly, the initiatives to promote PLS financing will, at least, not necessarily have a detrimental effect on the net margin. Operating expenses matter more, underscoring the need for serious efforts to improve the effectiveness of Islamic local banks’ cost management.